Gambaran Kelelahan pada Pasien Gagal Jantung - Bambang Aditya Nugraha; Sandra Pebrianti; Hesti Platini (Jurnal Medika Cendikia, 2018)
Heart failure are heart inability to maintain both systemic and pulmonary circulation. In congestive heart failure circulatory failure occures, characterized by jugular venous congestion in the cervical area. Circulatory failure causes changes in the body's metabolism and energy formation resulting in chronic fatigue. The purpose of the study was to describe fatigue in patients with congestive heart failure at Garut District Government Hospital. The research design is descriptive. The sampling technique using concecutive sampling as much as 30 respondents. Instrument for measuring fatigue using Fatigue Assessment for Chronic Illness Therapy (FACIT) Fatigue Scale. The results showed that fatigue level of patients who experience congestive heart failure mostly in the category of mild fatigue as 7 people (26%) and as 23 people (76%) are in the category of severe fatigue. The conclusion of this study is the level of fatigue of respondents mostly in the severe category.